Optimization of Synchronous Non-Isolated Bidirectional DC-DC Switching Power Converter - Mahesh Gowda, N. M.; Parthasarathy, S. S. (Asian Journal of Electrical Sciences, 2016)
This paper presents a high-efficiency non-isolated synchronous bidirectional DC-DC switching power converter. The circuit is made to operate in Synchronous Discontinuous Conduction Mode (SDCM)/Forced Continuous Conduction Mode (FCCM) of operation for minimum inductor value, to reduce the size, weight and cost of the converter. A snubber capacitor is used across the switch to minimize turn-off loss. The power dissipation through snubber capacitor and inductor is minimized by proper selection of their value, which improves the efficiency of the converter. Complementary gate signals are used to control the ON and OFF of main and auxiliary switch. By use of SDCM of operation, complementary gate signals control scheme and snubber capacitor, turn-on loss and parasitic ringing effect is minimized. State space averaging method is used to obtain control-to-current transfer function module. Using the transfer function module, Proportional Integral Derivative (PID) controller is tuned using PID tuner software, available in MATLAB simulink control design block to regulate load voltage and load current for change in inductor reference current (I*), change in load resistance and change in input voltage. The modules are verified using MATLAB simulink simulator.